2010
DOI: 10.1097/scs.0b013e3181f3c76c
|View full text |Cite
|
Sign up to set email alerts
|

Management of Myofascial Pain

Abstract: The present study was designed to compare the effects of low-level laser with occlusal splints in patients with signs and symptoms of myofascial pain (MP) dysfunction syndrome. A total of 40 (34 women and 6 men, with a mean age of 32.84 [SD, 10.70] years) were selected after the diagnosis of MP according to the Research Diagnostic Criteria for Temporomandibular Disorder. The patients were randomly divided into 2 groups: study group (n = 20) and control group (n = 20). Low-level laser was applied to patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
53
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 32 publications
2
53
3
1
Order By: Relevance
“…Analgesic effects of laser in case group compared with control group was statistically significant. Our findings were not in line with those of Öz et al, 24 Dundar et al, 25 Altan et al, 26 and Hansen et al 27 The afore mentioned studies used different wavelengths and powers of laser and had different sample sizes and variable number of treatment sessions. However, they all had a case control design and yielded similar results.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Analgesic effects of laser in case group compared with control group was statistically significant. Our findings were not in line with those of Öz et al, 24 Dundar et al, 25 Altan et al, 26 and Hansen et al 27 The afore mentioned studies used different wavelengths and powers of laser and had different sample sizes and variable number of treatment sessions. However, they all had a case control design and yielded similar results.…”
Section: Discussioncontrasting
confidence: 57%
“…Since they did not obtain favorable results and based on the suggested energy density values for GaAsAl laser, 30 we used a lower energy density. In the study by Öz et al, 24 3 J/cm 2 and in the study by Hansen et al, 27 4.7 and 9.4 J/cm 2 energy densities were chosen. Based on their findings, we selected a higher energy density.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Öz et al . [13] demonstrated that low-level laser therapy is as effective as occlusal splint in pain release and mandibular movement improvement. A study by Kulekcioglu et al .…”
Section: Discussionmentioning
confidence: 99%